Volunteering benefits life satisfaction over 4 years: The moderating role of social network size. (6th August 2018) - Jiang, Da; Hosking, Diane; Burns, Richard; Anstey, Kaarin J.
Abstract : Objectives: Social engagement benefits emotional well‐being, but the mechanisms need to be better understood. Using volunteering as an example of social engagement, we first examined whether volunteering would be longitudinally beneficial to life satisfaction in older adulthood and the moderating role of changes in the social network size in such a relationship as a potential mechanism. Second, we investigated motivations to volunteer in order to promote more volunteering in older adulthood. Methods: A sample of 1, 591 older participants from the Personality and Total Health (PATH) through life study (PATH) was assessed (Age: Mean = 66.54 years, SD = 1.50 years, 48% female). PATH is a four‐wave longitudinal project with a 4‐year interval between each two waves. Data from PATH Waves 3 and 4 were used to examine the relationship between volunteering and life satisfaction changes and the moderating role of changes in the social network size. Data from PATH Waves 2, 3, and 4 were used to examine the motivations to short‐term and long‐term volunteer. Results and Conclusion: We found that longer volunteering time was associated with a higher level of increase in life satisfaction during the 4‐year interval. Life satisfaction increased more in participants who lost more friends than in participants who lost fewer friends. Consistent with socioemotional selectivity theory, emotional goals were positively associated with more short‐term and long‐term volunteering behaviours. These findings provide scientific insight into the mechanisms and motives underlying the positive effects of volunteering on life satisfaction in old age.